Contrasting Regional Environmentalisms in the Eastern Mediterranean: A social Constructionist Perspective - Stuart Schoenfeld; Jonathan Rubin (L'Espace Politique)
Regionalism, as a socio-political project, involves the social production of knowledge; common interests are identified and a common identity around these shared interests is promoted. In the Eastern Mediterranean three projects of transnational environmental cooperation construct geographically different regions – a region with Israel, the Palestinian Territories and Jordan at the center, the Mediterranean, and the Arab region. The analysis of these contrasting projects draws on literature on framing, Middle East regionalism and regional environmental governance. The review asks whether these contrasting initiatives are competing or part of a dynamic process in which they positively reinforce each other.